2011
DOI: 10.1186/1475-2891-10-82
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and antioxidant effects of dietary black sesame meal in pre-hypertensive humans

Abstract: BackgroundIt has been known that hypertension is an independent risk factor for cardiovascular disease (CVD). CVD is the major cause of morbidity and mortality in developed and developing countries. Elevation of blood pressure (BP) increases the adverse effect for cardiovascular outcomes. Prevention of increased BP plays a crucial role in a reduction of those outcomes, leading to a decrease in mortality. Therefore, the purpose of this study was to investigate the effects of dietary black sesame meal on BP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 34 publications
(43 reference statements)
1
42
0
Order By: Relevance
“…Consistent with these observations, ingestion of sesame seeds has been demonstrated to reduce oxidative stress in rats 42 and humans 43,44 . In the present study, we confirmed the results of a previous study 42 that sesame seeds reduced serum concentrations of malondialdehyde in rats.…”
Section: Discussionsupporting
confidence: 65%
“…Consistent with these observations, ingestion of sesame seeds has been demonstrated to reduce oxidative stress in rats 42 and humans 43,44 . In the present study, we confirmed the results of a previous study 42 that sesame seeds reduced serum concentrations of malondialdehyde in rats.…”
Section: Discussionsupporting
confidence: 65%
“…In a group of 13 mild hypertensive subjects, 60 mg of sesamin for 4 wk lowered SBP 3.5 mmHg (p < 0.044) and DBP 1.9 mmHg (p < 0.045) [258] . Black sesame meal at 2.52 g/d over 4 wk in 15 subjects reduced SBP by 8.3 mmHg (p < 0.05) but there was a non-significant reduction in DBP of 4.2 mmHg [259] . Sesame oil at 35 g/d significantly lowered central BP within 1 h and also maintained BP reduction chronically in 30 hypertensive subjects, reduced heart rate, reduced arterial stiffness, decreased augmentation index and pulse wave velocity, decreased HSCRP, improved NO, decreased endothelin-Ⅰ and improved antioxidant capacity [264] .…”
Section: Sesamementioning
confidence: 99%
“…Sesame has been shown to reduce BP in a several small randomized, placebo controlled human studies over 30-60 d [256][257][258][259][260][261][262][263][264] . Sesame lowers BP alone [257][258][259][260][261] or in combination with nifedipine [256,260] diuretics and beta blockers [257,261] .…”
Section: Sesamementioning
confidence: 99%
See 1 more Smart Citation
“…Amutha and Godavari (2016) demonstrated that S. indicum can be used to reduce the postprandial hyperglycemia by inhibiting carbohydrates metabolizing enzymes α-amylase and α-glucosidase, and also to combat the free radicals due to its antioxidant activity. It has been reported that sesame seeds can improve oxidative status due to the activities of their contents including sesamin, sesamolin, sesamol, and sesame (Wichitsranoi et al, 2011).…”
Section: Sesamum Indicummentioning
confidence: 99%